Let y = y(x) be a f...
 
Notifications
Clear all

[Solved] Let y = y(x) be a function of x satisfying y√(1 - x^2) = k - x√(1 - y^2) where k is a constant and y(1/2) = - 1/4. Then dy/dx at x = 1/2, is equal to  

  

1

Let y = y(x) be a function of x satisfying y√(1 - x2) = k - x√(1 - y2) where k is a constant and y(1/2) = - 1/4. Then dy/dx at x = 1/2, is equal to

(a) √5/2

(b) -√5/2

(c) 2/√5

(d) -√5/4

This topic was modified 4 months ago by puja
Topic Tags
1 Answer
1

Correct option: (2)

Explanation:

Put x = sinθ, y = sin α

 
2s

Share: